China and International Crises: The Problem of Hedging and Aid: A Reading of the Wars in Ukraine and Gaza - Attarid Awadh Abdulhameed (Tikrit Journal For Political Science, 2025)
Perhaps the strategy of strategic hedging or anticipation is one of the essences of the Chinese heritage that leans strongly on wisdom and patience, mixing in it the teachings of Confucius, the art of war (Latzu), and the teachings of the architect of the Chinese Renaissance (Deng Xiaoping), who recommends seeing, waiting, observing, and not claiming leadership, to create precaution in order for China to avoid confrontation with the West. As long as it is in the midst of its rise and advancement to achieve the Chinese dream, which will place it in another position and position that will restore its glory by being the “Kingdom of Heaven,” as the early Chinese called it This advanced understanding and strategic awareness remains a Chinese mantra that decision-makers adopt, in moving aside from any direct intervention in international crises, in which the other party is, The West, especially the United States, is striving to stop the momentum of the Chinese renaissance, and to the extent that some crises pose great importance to China, whether in its orientations or in its vision of the nature of the international system, which was formulated by the West to serve reconciliation, China continues to seek to disengage with the leading power and its European sisters, through the gate of peace, cooperation and negotiation, seeking to define its role as a major country that aspires to impose peace and stability and enhance mutual dependence.